Measures of satisfaction with care during labour and birth: a comparative review - Sawyer, Alexandra; Ayers, Susan; Abbott, Jane; Gyte, Gillian; Rabe, Heike; Duley, Lelia (BioMed Central, 2013)
Background Satisfaction is the one of the most frequently reported outcome measures for quality of care. Assessment of satisfaction with maternity services is crucial, and psychometrically sound measures are needed if this is to inform health practices. This paper comparatively reviews current measures of satisfaction with care during labour and birth.